Penentuan Effort Rate Pada Estimasi Effort Menggunakan Metode Use Case Point Untuk Pengembangan Perangkat Lunak Website Kepemerintahan - Wahyu Kurniawan; Sholiq Sholiq; Teguh Sutanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2013)
Abstract: Effort estimation using Use Case Point (UCP) method obtained from the multiplication of the UCP with the Effort Rate (ER). Some studies conclude that there is some value of ER used in the calculation of effort estimation. However, the most often used is the ER with value 20 man-hours given by Karner. Disputes about the research that is ER by Karner occurred in 1993, so it is possible that the ER by Karner not suitable when applied in the calculation of effort estimation for the project worked on in 2013 and the years to come. This study used 8 data of governance website software development projects. The data is used to calculate actual effort, making use case diagrams, and calculations UCP estimation. Further level of analysis that is performed correlation and regression equations for actual effort and the UCP estimation. Based on the regression equation then performed calculations tangent ? to produce the ER. From this research produced the ER as big as 5,178 man-hours. The ER is much smaller than the value given by Karner ER. Case is possible for several reasons, among others: 1) Enginering software technology that is growing rapidly. 2) Manufacturing website using components. 3) Source of the internet so complete. Keywords: Effort Rate (ER), Effort Estimation, Use Case Point (UCP), Governance Website